What happened to the lapse of administrative procedures?: a case law review in light of a 'new standard' from the Supreme Court - Araya Avila, Nicolas (Revista de Derecho Público, 2024)
The present jurisprudential review examines a new criterion applied by the Supreme Court, by virtue of which it dismissed the application of the doctrine of procedural abandonment, indicating that an unjustified delay by the Administration in processing a procedure constitutes a material impossibility of continuing with it. In this regard, it is noted that this new criterion represents a synthesis and consolidation of the jurisprudential development regarding unjustified delays. However, it is observed that this criterion has not been fully replicated in subsequent rulings, as there are resistances that advocate for the application of the doctrine of procedural abandonment.